Design of Augmented Reality Book for Economic Mathematics Course - Buchori, Achmad; Istiyaningsih, Rumiyatun (Dinamika Pendidikan, 2018)
The type of this research is a development research that aims to produce android-based learning media using AR on a economic mathematic which is feasible to use and can easily know the results of students learning ability. The method used is ADDIE method which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. Data analysis was done by normality test, homogeneity test, t test, and learning mastery test. The results of this study concluded that (1) the results for the percentage of media expert validation amounted to 89.2%, material experts 86.1% and learning design experts 87.5% with the criteria of each very good. (2) the result of practicality test based on student response obtained percentage equal to 88,9% with very good criterion. (3) data from the field show that the learning outcomes of students who obtain android-based learning media using AR better than students using learning by lecturing method (conventional learning).